Adaptive public spaces. Exploring digital transition for social and environmental benefit - Bianca Andaloro; Martijn de Waal; Frank Suurenbroek (Agathón)
The present social and environmental challenges, the impact of climate change and the pandemic, revealed the urgency and the opportunity to rethink urban design through its renewed spaces and temporalities. The pandemic offered a ‘natural experiment’ to explore and develop new perspectives, making public spaces more resilient. Contributing towards a rethink of these spaces, the present paper explores adaptive architecture with responsive technologies and their capability of shaping public spaces to constitute a conversation piece with the surrounding environment. This approach combines and reflects different disciplinary fields: architecture, civic interaction and urban design. The exploration works around a speculative design case – produced as part of broader research at the Amsterdam University of Applied Science in collaboration with the Master in Digital Design.